FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI MAHASISWA AKUNTANSI DALAM MEMILIH PROFESI AKUNTAN PUBLIK DI UNIVERSITAS GRESIK - Suparman, Petrus; Sholichah, Sholichah (Fakultas Ekonomi Universitas Gresik, 2017)
Public accounting profession is considered to be able to provide the opportunity for individuals or private to develop skills and provide opportunities to gain varied work. This is because they assume will be assigned in various sections or positions on the various types of companies that have different characteristics. Therefore, this study aims to determine wether factors such as financial rewards, professional training, social values, and labor market considerations influence the selection of the public accounting profession for accounting students at the Gresik University.Populations in this study were students majoring in accounting Gresik University economic faculties. Samples in this study using a quota sampling as many as 50 students majoring in accounting who have followed the course of auditing. Analysis techniques used are validity testing, reliability testing, multiple linier regression, F test and t test. The data used are primary data collected for the study of the place of the incident example distributing questionnares. While secondary data in this research is through review of literature, example from books, journals, and access the web site. The result of research indicate the factors of financial rewards, professional training, social values, and labor market considerations simultaeously and partially affect the interests of accounting students in selecting the profession of public accountants.ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3477689